Clinical assessment compared with breathalyser readings in the emergency room: concordance of ICD-10 Y90 and Y91 codes. Issue 10 (27th September 2005) - Cherpitel, C; Bond, J; Ye, Y; Room, R; Poznyak, V; Rehm, J; Peden, M
Abstract : Objectives: The purpose of this study was to analyse the validity of clinical assessment of alcohol intoxication (ICD-10 Y91) compared with estimated blood alcohol concentration (BAC) using a breath analyser (ICD-10 Y90) among patients in the emergency room (ER). Methods: Representative samples of ER patients reporting within six hours of injury (n = 4798) from 12 countries comprising the WHO Collaborative Study on Alcohol and Injuries were breath analysed and assessed blindly for alcohol intoxication at the time of ER admission. Data were analysed using Kendall's Tau-B to measure concordance of clinical assessment and BAC, and meta analysis to determine heterogeneity of effect size. Results: Raw agreement between the two measures was 86% (Tau-B 0.68), but was lower among those reporting drinking in the six hours prior to injury (raw agreement 39%; Tau-B 0.32). No difference was found by gender or for timing of clinical assessment in relation to breath analysis. Patients positive for tolerance or dependence were more likely to be assessed as intoxicated at low levels of BAC. Estimates were homogeneous across countries only for females and for those negative for alcohol dependence. Conclusions: Clinical assessment is moderately concordant with level of BAC, but in those patients who have actually been drinking within the last six hours the concordance was much less, possibly because, in part, of a tendency on the part of clinicians to assign some level of intoxication to anyone who appeared to have been drinking.